2021
DOI: 10.4102/safp.v63i1.5253
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of hospitalised COVID-19 patients at Mthatha Regional Hospital, Eastern Cape, South Africa: A retrospective study

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a public health crisis that threatens the current health system. The sudden expansion in the need for inpatient and intensive care facilities raised concerns about optimal clinical management and resource allocation. Despite the pressing need for evidence to make context-specific decisions on COVID-19 management, evidence from South Africa remained limited. This study aimed to describe the clinical characteristics and outcomes of COVID-19 hospitalised patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Mortality among patients admitted with COVID-19 was 38%, which is comparable with data from other countries in the region [ 26 28 ]. Of note, 21% of deaths occurred within 24 hours of admission and may have been avoidable if patients had presented earlier.…”
Section: Discussionsupporting
confidence: 81%
“…Mortality among patients admitted with COVID-19 was 38%, which is comparable with data from other countries in the region [ 26 28 ]. Of note, 21% of deaths occurred within 24 hours of admission and may have been avoidable if patients had presented earlier.…”
Section: Discussionsupporting
confidence: 81%
“…Moderate/severe chest radiograph changes were evident in 278 (90.0%) participants. The median Horowitz Index 8 (ratio of arterial partial pressure of oxygen to fraction of inspired oxygen the patient is receiving: PaO 2 /FiO 2 ) was 125 (IQR: 75–250), with 40.9% of participants having a Horowitz Index 9 less than or equal to 100, indicating severe acute respiratory distress syndrome (ARDS) on presentation. Biochemical derangements included a median urea of 9.4 (IQR: 5.9–17.1), median creatinine of 112 (IQR: 80–208) and a median glomerular filtration rate (GFR) of 47 (IQR: 25–82).…”
Section: Resultsmentioning
confidence: 99%
“…Nine further studies reported descriptive statistics on COVID-19 mortality and hypertension or CVD but did not calculate statistics to formally compare groups. 15,24,26,29,35–39…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies did not calculate statistics to compare those with and without preexisting hypertension or CVD on COVID-19 outcomes. [21][22][23][24][25][26][27][28][29][30]…”
Section: Covid-19 Infection and Severitymentioning
confidence: 99%
See 1 more Smart Citation